INTEGRATION OF RELIGION AND SCIENCE IN BIOLOGY COURSES AT SMA 4 PADANGSIDIMPUAN - Muthiatul Khairiyah Rtg; Anhar (ONTOLOGI : JURNAL PEMBELAJARAN DAN ILMIAH PENDIDIKAN, 2024)
This study aims to examine the integration of religion and science in Biology learning at SMA 4 Padangsidimpuan, by highlighting the problems, objectives, and application of qualitative research methods in analyzing the relationship between the two. The integration of religion and science in education is often considered difficult, especially in Biology lessons which are usually seen as contradictory to religious teachings. Therefore, this study aims to determine how Biology teachers at SMA 4 Padangsidimpuan connect religious values ​​in science teaching, and how students respond to this approach. This study uses a qualitative approach with a case study type. Data were collected through observation, in-depth interviews with Biology teachers, and analysis of curriculum documents and teaching materials applied. In addition, interviews were also conducted with students to determine their views and attitudes towards Biology learning that combines religious elements. The results of the study indicate that Biology teachers at SMA 4 Padangsidimpuan integrate religious values ​​with Biology materials by connecting the natural phenomena studied with religious concepts, such as creation by God, the balance of nature, and human responsibility in protecting the environment. The methods used include discussion, reflection, and providing real examples that link religious teachings with scientific theories. In conclusion, the integration of religion and science in Biology learning at SMA 4 Padangsidimpuan provides a more comprehensive understanding for students, where they not only learn scientific concepts, but also appreciate the relationship between science and religious teachings in their lives. This approach enriches students' insights and fosters positive attitudes towards both fields.